SISTEM PENJAMINAN MUTU PEMBELAJARAN JARAK JAUH DI PERGURUAN TINGGI DI MASA PANDEMI COVID-19 - Subijanto; Budi Kadaryanto; Nur Berlian Venus Ali; Agus Amin Sulistiono; Ferdi Widiputera; Ika Asri Dwi Martini (usat Standar dan Kebijakan Pendidikan, BSKAP, Kemendikbudristek, 2021)
Disruption in higher education due to the impact of Covid-19 pandemic has forced universities to adapt to distance learning by utilizing information and communication technology. At the same time, the quality of learning must be maintained and prioritized. The problem discussed in this study is that there is no standard for quality assurance of distance learning in the wake of Covid-19 pandemic for higher education. This study aims to (1) analyze policies related to distance learning quality assurance and (2) analyze the efforts made by universities in implementing quality assurance. This study is desk research where the analysis is carried out in two stages. The first stage is to review policies related to distance learning quality assurance, and the second stage is to analyze the implementation of quality assurance in three state universities and five private universities. The results show that (a) the implementation of the Internal Quality Assurance System varies, and (b) there is no standard that can be used as a reference to ensure the quality of distance learning. This study concludes that the strengthening of internal quality assurance system through the cycle of determination, implementation, evaluation, control, and improvement can be used as an alternative to quality assurance for distance learning in higher education.